Exploration of Artificial Intelligence (AI) Application in Higher Education: A Research Study in Kolaka, Southeast Sulawesi - Sallu, Sulfikar; Raehang, Raehang; Qammaddin, Qammaddin (Information Technology and Science (ITScience), 2024)
This article explores the implementation of Artificial Intelligence (AI) in higher education in Kolaka, Southeast Sulawesi. The research aims to identify and analyze how AI can be used to enhance the learning process and academic administration in universities. The research method includes primary data collection through interviews and observations, as well as secondary data from academic sources. The results show that AI contributes significantly to operational efficiency and the learning experience. This research provides new insights into the application of AI in the academic environment and offers recommendations for higher education institutions that want to integrate AI technology